2018
DOI: 10.15171/jcvtr.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of short-term mortality after acute stroke in East Azerbaijan province, 2014

Abstract: Introduction: Stroke is one of the important causes of death and disability in Iran. This study aimed to examine the factors influencing the short-term mortality of stroke in Northwest of Iran. Methods: Study population were all patients with confirming the diagnosis of the first-ever stroke who were hospitalized in two referral teaching hospitals from October 2013 to March 2015. They were followed up to 30 days after onset of stroke. A neurology year three resident was responsible for extracting the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…In addition, the findings of Shamshirgaran et al indicated that 13.2% of deceased people due to stroke had a positive family history of stroke. 26 Additionally, in a 5-year research study of stroke mortality, Lambert et al concluded that 11.1% of deceased people had a family history of stroke, 27 which contradicts the results of the present study. The reason for this conflict in findings may be the illiteracy of the majority of the examined patients and their lack of awareness of having a family history of stroke.…”
Section: Discussioncontrasting
confidence: 91%
“…In addition, the findings of Shamshirgaran et al indicated that 13.2% of deceased people due to stroke had a positive family history of stroke. 26 Additionally, in a 5-year research study of stroke mortality, Lambert et al concluded that 11.1% of deceased people had a family history of stroke, 27 which contradicts the results of the present study. The reason for this conflict in findings may be the illiteracy of the majority of the examined patients and their lack of awareness of having a family history of stroke.…”
Section: Discussioncontrasting
confidence: 91%
“…This provides important implications for the clinicians to target the high-risk patients for the specific therapies and management strategies. 7 We found that in expired patients, mean NIHSS score was 21.6 ± 5.08 which was remarkably high and statistically significant.…”
Section: Discussionmentioning
confidence: 61%
“…The incorporated studies were from 1998 to 2018, and only 13 provinces had at least one eligible study. Based on the geographical location of the province, out of 28 studies included, six were in Khorasan Razavi [22][23][24][25][26][27], 6 in East Azerbaijan [14,16,17,[28][29][30], 3 in Isfahan [31][32][33], 2 in Tehran [34,35], 2 in Qom [13,36], and 2 in Ardabil [34,35,37,38]. Guilan [39], Kermanshah [40], South Khorasan [41], Mazandaran [42], Fars [15], Urmia [43], and Zahedan [44] Semnan [45] each had 1 study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Stroke mortality can be an excellent indicator of stroke care and control. Several studies have been conducted to estimate the mortality rate of stroke in hospitals, including 30 days post-stroke [14,15], six months post-stroke [16], and long periods with different sample sizes and different follow-up lengths in several provinces of Iran [17]. Identification of mortality predictors at the time of hospitalization can be beneficial in reducing post-stroke mortality rates.…”
Section: Introductionmentioning
confidence: 99%